Homobinuclear Mixed Ligand Complexes of Alkali Metal Salts of Some Organic Compounds with Bis(8-Hydeocy-5-Quniolyl) - Prakash, Dharm; Pd. Roy, Amarendra; Prakash Gupta, OM (Asian Journal of Chemistry, 2010)
A number of complexes of the composition (ML)2·H2L´, where M = Li, Na or K, L = deprotonated 2,4-dinitrophenol, 2,4,6-trinitrophenol, 5,7-dinitro-oxine, 5,7-dichloro-oxine, 5,7-dibromo-oxine and 2-methyl-oxine and H2L´ = bis(8-hydroxy-5-quinolyl) methane, have been synthesised and characterised on the basis of elemental analysis, conductance and infrared spectral data.